1992
DOI: 10.1366/0003702924125591
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Generation of Quasi-Continuous, Tunable Ultraviolet Excitation for Raman Spectroscopy: Applications to Drug/Nucleotide Interactions

Abstract: We demonstrate the generation of quasi-continuous ultraviolet excitation at wavelengths shorter than 240 nm using the frequency-doubled output of a synchronously pumped picosecond dye laser operating in the region of 420 nm. Owing to the relatively low peak power but high average power of the system, we obtain high-quality resonance Raman spectra at wavelengths as short as 209 nm. We apply the source to the study of the binding of anticancer drugs to DNA. In particular, we compare the binding of cis-diamminedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Gustafson and co-workers demonstrated the generation of quasi-CW ultraviolet excitation below than 240 nm using the frequency-doubled output of a synchronously pum ped MHz picosecond dye laser operating in the 420 nm region. 12 Recently, Doig and Prendergast developed a continuously tunable source via tripling or quadrupling a mode-locked ; 2 ps Ti : sapphire (Ti : S) laser, which has a high duty cycle and good tunability. 13 However, the laser linewidth is about 10 ±15 cm 2 1 , which is too broad for m any UVRR applications.…”
Section: Introductionmentioning
confidence: 99%
“…Gustafson and co-workers demonstrated the generation of quasi-CW ultraviolet excitation below than 240 nm using the frequency-doubled output of a synchronously pum ped MHz picosecond dye laser operating in the 420 nm region. 12 Recently, Doig and Prendergast developed a continuously tunable source via tripling or quadrupling a mode-locked ; 2 ps Ti : sapphire (Ti : S) laser, which has a high duty cycle and good tunability. 13 However, the laser linewidth is about 10 ±15 cm 2 1 , which is too broad for m any UVRR applications.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation in the deep UV is particularly important because resonance with amide -* transitions enhances amide backbone vibrations that are sensitive probes of protein secondary structures. [5][6][7][8][9][10] Earlier deep UV lasers were based on harmonic generation of dye lasers, or of the Nd-YAG laser, with Raman shifting in H 2 , D 2 , or CH 4 gases. The frequency doubled outputs of continuous wave (CW) Ar ϩ , Kr ϩ , and hollow cathode lasers have also been used.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational modes in established intercalators such as pyrene and daunomycin, well-known groove binders such as netropsin, covalent binders such as cis -platin, , as well as nucleic acids themselves , have been measured by infrared absorption and Raman (resonant and nonresonant) scattering using ultraviolet excitation. These studies have shown that significant changes in the vibrational degrees of freedom in both the binding drug and DNA occur when the two are combined.…”
Section: Introductionmentioning
confidence: 99%